Exogenous and Endogenous Spatial Growth Models - Frans Bal; Peter Nijkamp (Tinbergen Institute, 1997)
In this paper, we investigate the impact on aggregate regional utility as a result of both exogenous growth and endogenous growth in a spatial system. We will first analyze the case of two closed regions, followed by the case of two open regions. The main instrument used in our approach to study the changes in collective regional welfare is Dynamic Programming. The traditional exogenous Solow growth model forms the basis of our paper. The analysis of this model will be extended to a comparison of two closed regions with exogenous growth. By introducing a case of a common labour market, we are able to investigate exogenous growth between two open regions. For the analysis of endogenous growth, we adopt the same structure as the one used for the investigation of exogenous growth models. In this framework, an investment in knowledge is considered as the endogenous driving force. Finally, we take a closer look at the timing of cost-reducing investments. In total, seven related but distinct cases are identified and studied in more detail.
Keywords: 330; Regionales Wachstum; Theorie